Weeding out the Dealers? The Economics of Cannabis Legalization - Emmanuelle Auriol; Alice Mesnard; Tiffanie Perrault (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We model consumer choices for cannabis in a risky environment and determine the supply of cannabis under prohibition and legalization. While introducing a legal market reduces the profits of illegal providers, it increases cannabis consumption. We show that this trade-off can be overcome by combining legalization with sanctions against users and suppliers of illegal products, and improvements to the quality of legal products. Numerical applications to the US highlight how our proposed policy mix can control the increase in cannabis consumption post-legalization and throttle the illegal market. The eviction prices we predict to drive dealers out of business are much lower than the prices of legal cannabis in the states that opted for legalization, leaving room for the black market to flourish. Analyzing the compatibility of several policy goals put forward in the public debate, including maximizing tax revenue and minimizing psychotropic consumption, we shed light on the less favorable outcomes of recent legalization reforms and suggest a new way forward.
Keywords: I18; K32; K42; L51; 330; cannabis; legalization; crime; policy; regulation